2019
DOI: 10.1111/jsr.12930
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute exposure to morphine on breathing variability and cardiopulmonary coupling in men with obstructive sleep apnea: A randomized controlled trial

Abstract: Opioid‐related deaths from respiratory depression are increasing but there is only limited information on the effect of morphine on breathing during sleep. This study aimed to detect and quantify opioid‐induced cardiorespiratory pattern changes during sleep in obstructive sleep apnea (OSA) patients using novel automated methods and correlate these with conventional polysomnography (PSG) measures. Under a randomized double‐blind placebo‐controlled crossover design, 60 male OSA patients attended two one‐night vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…Thus, OIRD involves reduced spiking during the percolation phase due, in part, to suppression of intrinsically driven pre-inspiratory spiking of Oprm1+ neurons and de-recruitment of neurons with synaptically driven, pre-inspiratory spiking activity. Thus, we predict that opioidinduced suppression of preBötC activity during the percolation phase underlies the prolonged and irregular durations between inspiratory efforts that are characteristic of OIRD in both mice and humans (Walker et al, 2007, Wu et al, 2020, Varga et al, 2020.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, OIRD involves reduced spiking during the percolation phase due, in part, to suppression of intrinsically driven pre-inspiratory spiking of Oprm1+ neurons and de-recruitment of neurons with synaptically driven, pre-inspiratory spiking activity. Thus, we predict that opioidinduced suppression of preBötC activity during the percolation phase underlies the prolonged and irregular durations between inspiratory efforts that are characteristic of OIRD in both mice and humans (Walker et al, 2007, Wu et al, 2020, Varga et al, 2020.…”
Section: Discussionmentioning
confidence: 97%
“…A total of 201 studies published before May 24, 2021, were identified through literature searching. Seven studies were retained for review after preliminary screening (Blake, Yew, Donnan, & Williams, 2009; Martins et al,2020; Rowsell et al, 2019, 2020; Tomazini Martins, Carberry, Gandevia, Butler, & Eckert, 2018; Wang et al, 2013; Wu et al, 2020), and three studies ( n = 132 patients) were deemed suitable for meta‐analysis (Blake et al, 2009; Rowsell et al, 2019; Wang et al, 2013; Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of the seven articles, two studies examined respiratory load detection, load magnitude perception, tactile sensation, and OSA phenotypes but not the outcome variables of interest (Martins et al,2020; Tomazini Martins et al, 2018,). Of the other five studies, two studied the same population (Rowsell et al, 2020; Wu et al, 2020) and examined breathing variability, cardiopulmonary coupling, and genetic variance but not the outcomes of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, OIRD involves reduced spiking during the percolation phase due, in part, to suppression of intrinsically driven pre-inspiratory spiking of Oprm1+ neurons and de-recruitment of neurons with synaptically driven, pre-inspiratory spiking activity. Thus, we predict that opioid-induced suppression of preBötC activity during the percolation phase underlies the prolonged and irregular durations between inspiratory efforts that are characteristic of OIRD in both mice and humans (Walker et al, 2007, Wu et al, 2020, Varga et al, 2020).…”
Section: Discussionmentioning
confidence: 97%